Physical Rigging Procedures Based on Character Type and Design in 3D Animation - Mohd Rosli, Arshad; Kim, Hae Yoon; Ahmad Azaini, Abdul Manaf; Muhammad Azmin, Mohamed Ghazali (Blue Eyes Intelligence Engineering Publishing, 2019)
In 3D (Three-Dimensional) animation pipeline, the term rigging is commonly used to describe the process of creating skeleton system inside the finishing 3D character geometry and assigning animation controllers for animators to animate the 3D character. In order to establish a fluidity movement on the character, the proper setting must be planned and the flexibility of the controller must be setup properly. However, the discussion and understanding about rigging setup for specific 3D characters from previous researcher is very limited. Hence, the process of rigging will take longer time to complete especially for novice rigger artist. This study will explore the fundamental process of character rigging system and identify the method and techniques for rigging characters based on their anatomy designs. The analysis of this study will look on the conceptual design of the character; how to implement proper techniques and workflow based on the primary and secondary data provided in this study. The findings in this paper indicate common techniques for human rig object in 3D characters is using Biped, CAT or auto rigs. From our experiment, we found biped or CAT rigging is the best setting for the animals and realism characters. Custom rig is suitable for cartoony characters. Rigging system for anthropomorphism character is a bit different from the human rigs system. Anthropomorphism character requires several modifications on their physical appearances in which adding or subtracting the limb that physically taken from specific animal or any objects. For this type of character, we suggested to use biped rigging system. However, for complex anthropomorphism characters with many form structures, the study of movement, exaggeration and bone limitation must be analyzed before deciding the proper technique for rigging. Hence, the chain rig system is the best option for this type of anthropomorphism character. Therefore, rigging in animation is the process assembling the skeleton system into the character. The use of proper rigging style will determine how the character move and pose in final animation.